Legal Dilemma of Abortion Regulation for Rape Victims in Indonesia from the Perspective of Justice - Iwansyah, Iwansyah; Arief Fakrulloh, Zudan (Asian Journal of Social and Humanities, 2024)
This research discusses the role and impact of medical expert witness testimony in drug abuse cases involving police officers as alleged violators of the code of ethics. Expert witness testimony plays a critical role as a key piece of evidence in the legal process, particularly in determining the validity of allegations and ensuring fairness in proceedings. However, the study highlights several challenges faced by medical experts, including social pressure, public stigma, and potential conflicts of interest that may compromise their objectivity, integrity, and independence. Furthermore, the complexity of legal procedures and administrative constraints can hinder the timely collection of biological samples and subsequent analysis. Difficulties in accessing relevant medical records and data further exacerbate these challenges, creating delays and inefficiencies in resolving cases. This study also underscores the psychological and institutional pressures on expert witnesses when handling cases involving law enforcement personnel, which can impact their professional credibility. To address these issues, the research recommends systemic reforms aimed at strengthening the role of expert witnesses through clearer regulations, standardized procedures for evidence collection, and enhanced safeguards to protect their independence. Improved transparency, accountability, and collaboration between legal and medical institutions are critical to ensuring justice, particularly in cases of drug abuse involving law enforcement officers.